Mary had a little lamb - Hale, Sarah Josepha Buell (Scholastic, 1990)
A contemporary interpretation of the well-known nineteenth-century nursery rhyme about the school-going lamb, accompanied by color photographs, a sample exercise from McGuffey's reader, and a note on the history of the author and her famous rhyme.